Liquid Chromatography-Tandem Mass Spectrometry Method for Determination of Homocysteine in Rat Plasma: Application to the Study of a Rat Model for Tauopathies - Kovac, Andrej; Svihlova, Katarina; Michalicova, Alena; Novak, Michal (Journal of chromatographic science, 2015)
Hyperhomocysteinemia is a common occurrence in many neurodegenerative diseases, including tauopathies. We developed and validated a simple and sensitive liquid chromatography-tandem mass spectrometry method for the analysis of homocysteine (Hcy) in rat plasma. Hcy was analyzed using ultra-performance liquid chromatography on a C8 column with detection by positive ESI tandem mass spectrometry. For optimal retention and separation, we used ion-pair reagent-heptafluorobutyric acid. The method utilizes heavy labeled internal standard and does not require any derivatization or extraction step. The procedure was validated in compliance with the European Medicines Agency guideline. The limit of detection was 0.15 µmol/L and the limit of quantification was 0.5 µmol/L. The method showed excellent linearity with regression coefficients higher than 0.99. The accuracy was in the range of 93-98%. The inter-day precision (n = 5 days), expressed as % relative standard deviation, was in the range 3-8%. Using this method, we analyzed plasma samples from two transgenic lines of the rat model for tauopathies.
Keywords: Reproducibility of Results; Rats; reprodukovatelnost výsledků; lineární modely; homocystein; Rats, Wistar; Limit of Detection; potkani inbrední SHR; studie případů a kontrol; limita detekce; Homocysteine; krysa rodu Rattus; Rats, Transgenic; Drug Stability; Linear Models; zvířata; Tandem Mass Spectrometry; Tauopathies; chromatografie kapalinová; stabilita léku; tauopatie; tandemová hmotnostní spektrometrie; potkani transgenní; potkani Wistar; Chromatography, Liquid; Rats, Inbred SHR; Case-Control Studies; Animals